Kedaulatan Laut Berbasis Sumberdaya Lokal: Perspektif Hak Asasi Manusia - Muhammad Heikal Daudy (Kanun Jurnal Ilmu Hukum, 2014)
The usage and management of the sea resources are still having classic obstacles either technical or structural. Aceh’s sovereign on the sea should be realized by the optimizing its resources wisely. For that reasons, the comprehensive understanding in terms of fulfilling Human Rights is relevant enough to be an indicator and it is part of state responsibility. This article aims to explain the reality of the sovereignty based on human right principle. Regarding to the management of the resources, the Aceh Government is taking part to manage and use it. Article 162 (1) of Aceh Governance Act states the Government and regional governments are entitled to manage the resources living in the territory. The development refers that, Aceh has great opportunity to develop its sovereignty. Thus, the state responsibility in fulfilling economic rights, social, and culture as demanded can be realized. The Sovereign of Sea Local Resources: Human Rights Perspective